Freshwater ascomycetes from north Maharashtra-III - Patil, S Y (International Multidisciplinary Research Journal, 2012)
The present paper deals with two species of Zopfiella Winter the freshwater ascomycetes viz. Zopfiella latipes (Lundq.) Malloch and Cain and Zopfiella submersa Guarro, Ai-Saadon, Gene and Abdullah were collected from the submerged wood samples from the various water bodies in North Maharashtra region. Zopfiella submersa Guarro, Al-Saadon, Gene and Abdullah is being recorded for the first time form India, while Zopfiella latipes (Lundq.) Malloch and Cain is being reported for the first time from North Maharashtra. Brief notes and illustration are given for each taxon. Geographical distribution of each species in India is also provided.